2016
DOI: 10.14713/pcsp.v12i3.1975
|View full text |Cite
|
Sign up to set email alerts
|

A Life-Saving Therapy: The Theory-Building Case of "Cora"

Abstract: The present paper presents a case study of long-term (121 sessions over three years), integrative therapy with "Cora," a client with a history of severe relational trauma that had led to difficulty in forming close relationships, and a history of hospitalization resulting from a series of suicide attempts. Despite these challenges, Cora reported a highly satisfactory outcome at the end of therapy. Using the format of a theory-building case study (McLeod, 2010;Stiles, 2007), qualitative analysis of session eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Halvorsen, Benum, Haavind, and McLeod's (2016) case study of Cora," we note the valuable questions it raises with regards to identifying and conveying effective elements of the therapeutic process when expert clinicians treat difficult cases, integrating the narrative case study with formal qualitative research in a relatively large sample of cases, and case study methodology in general. We examine the unique authorial voice of the case study, in this instance not that of the treating clinician; and we review some of the difficulties that arise from the authorial voice chosen for readers seeking to understand treatment process and its results.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Halvorsen, Benum, Haavind, and McLeod's (2016) case study of Cora," we note the valuable questions it raises with regards to identifying and conveying effective elements of the therapeutic process when expert clinicians treat difficult cases, integrating the narrative case study with formal qualitative research in a relatively large sample of cases, and case study methodology in general. We examine the unique authorial voice of the case study, in this instance not that of the treating clinician; and we review some of the difficulties that arise from the authorial voice chosen for readers seeking to understand treatment process and its results.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…A second superordinate theme Halvorsen et al (2016) found was that of courage. I am pleased to see that their case of Cora found evidence of client courage.…”
Section: Couragementioning
confidence: 99%
“…As noted by the Halvorsen et al (2016), Elliott et al (2009) have also noticed that quantitative and qualitative results do not always coincide. Elliott et al studied a client with a fear of driving over bridges.…”
mentioning
confidence: 92%
See 2 more Smart Citations